Pravastatin-Induced Eczematous Eruption Mimicking Psoriasis - Michael P. Salna; Hannah M. Singer; Ali N. Dana (Case Reports in Dermatological Medicine)
Background. Statins, an example of the most commonly prescribed medications to the elderly, are not without side effects. Dermatologic events are often overlooked as arising from medications, particularly those which are taken chronically. Moreover, elderly patients are prone to pharmacologic interactions due to multiple medications. In this report, we describe a case of a statin-induced eczematous dermatitis with a psoriasis-like clinical presentation and review the skin manifestations that may arise from statin therapy. Case Presentation. An 82-year-old man with gout and hypercholesterolemia presented to dermatology clinic with new onset of pruritic, scaly erythematous plaques bilaterally on the extensor surfaces of his arms. He had never had similar lesions before. Despite various topical and systemic treatments over several months, the rash continued to evolve. The patient was then advised to discontinue his long-term statin, which led to gradual resolution of his symptoms. He was subsequently diagnosed with statin-induced eczematous dermatitis. Conclusions. This case report describes an adverse cutaneous reaction to statins that is rarely reported in the literature. Medications, including longstanding therapies, should be suspected in cases of refractory dermatologic lesions.